Microfilm and digitization as choices in preservation - de Lusenet, Yola (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
The first conference the European Commission on Preservation and Access (ECPA) organized, 'Choosing to preserve', took place in Leipzig in 1996. For the keynote lecture we had invited a scholar, Professor Bernhard Fabian. This was a very deliberate choice, as the ECPA subscribed to the view that academic researchers, as users of the resources kept in libraries and archives, have to be involved in discussions about their preservation. The conference had attracted quite a crowd, around 150 people who were of course all there for the opening lecture. We invited Professor Fabian because he was a very good speaker, who could really present a convincing case to an audience, which he did also on that occasion. He devoted a large part of his presentation of 45 minutes to the horrors of microfilm, showing us pictures of illegible film, with bits missing, that was impossible to use. He explained how distressing it was for scholars to be forced to use surrogates that don't do justice to the originals that they need to study.